La persistencia del lenguaje religioso en el discurso político. El caso de Hugo Chávez. (2013)
From different perspectives there has been an attempt to put limits on the use of religious language in public discourse; with arguments like the defense of secularism or pluralism. The German philosopher Jürgen Habermas has argued that the religious discourse can share in the social debate after a translation of its principles into universally acceptable secular terms. However; the persistence of religious language in politics is still able to communicate successfully; and remains a valuable resource even in a socialist-style left like that of President Hugo Chavez. The purpose of this article is to analyze the discourse relationship between politics and religion from the example of the Venezuelan government.